Redefining terrorism: can State Actors commit and be responsible for acts of terrorism? - Njuguna, Catherine Wanjiru (Department of Public Law, 2023)
This dissertation seeks to give a more extensive definition of terrorism through a more innovative interpretation and use of the existing international legal systems, while not jeopardizing its foundations in the process. The dissertation also undertakes a proper evaluation of the elements of terrorism. The research study tests the hypothesis that states can commit terrorism. The aim of the dissertation is to demonstrate the need to redefine terrorism comprehensively in the international sphere and establish whether state actors can commit acts of terrorism. The study adopts a discourse analysis to investigate the research questions and puzzle out the exclusion of ‘state terrorism' from the discussion of terrorism in the mainstream literature while focusing on representative politics. In the instant case, the consequences of recognizing terror acts by non-state actors and not by the State or its agents. From the analysis and preceding discussions, this study affirms that excluding states or their agents as potential perpetrators of terrorism is a deliberate representation without a proper legal backup and that most definitions fail to appreciate the objective test in defining terrorism.